Synthesis, mechanical properties and fire behaviors of rigid polyurethane foam with a reactive flame retardant containing phosphazene and phosphate. (December 2015) - Yang, Rong; Hu, Wentian; Xu, Liang; Song, Yan; Li, Jinchun
Abstract: Reactive flame retardant hexa-(phosphite-hydroxyl-methyl-phenoxyl)-cyclotriphosphazene (HPHPCP) was synthesized by hexachlorocyclotriphosphazene, diethyl phosphite and p -hydroxybenzaldehyd. Flame retardant rigid polyurethane foams (FR-RPUFs) were prepared by free foaming with incorporating HPHPCP with polyether polyol, polyester polyol and polymethylene polyphenyl isocyanate. The chemical structure of HPHPCP was characterized by proton and 31 P nuclear magnetic resonance. The morphology, physical–mechanical properties, thermal stability and flame-retardant performance of rigid polyurethane foam (RPUF) and FR-RPUFs were investigated. Results suggested that the incorporation of HPHPCP into RPUF enhance the density, comprehensive strength and thermal stability as a result of higher crosslink concentration resulting from the multifunctional group of HPHPCP. Furthermore, with the increase of HPHPCP content, the limiting oxygen index (LOI) increased along with the gradually decreased values of the second peak heat release rate (PHRR2). In addition, when the additive of HPHPCP was higher than 10 wt%, FR-RPUFs pass UL-94 HF-1 rating and the flame spread limited simultaneously, indicating the reinforced and flame-retardant RPUFs could be obtained.